Sunday

April 20, 2014

April 20, 2014

Posted by **Kimi** on Sunday, January 23, 2011 at 5:46pm.

f(0)

f(-1)

f(2)

- Algebra -
**Jen**, Sunday, January 23, 2011 at 6:26pmf(x)=4x^-5x

f(0)

f(-1)

f(2)

All you have to do is put the number given in for x. I will do the first one for you.

4(0)^-5(0)

0^0=1

- Algebra -
**Kimi**, Sunday, January 23, 2011 at 6:28pmThanx!!

**Related Questions**

algebra - find the indicated outputs for f(x)= 4x^2- 5x= f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)= 4x-5x= f(0)= f(-1)= f(2)=

Algebra 1 - Find the indicated outputs for f(x)=4x(2)-5x f(0)=? f(-1)=? (f(2)=?

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

algebra - Find the indicated outputs for f(x) =4x^2 -4x f(0) f(-1) f(2)

algebra - Find the indicated outputs for f(x)=4x^2 -4x f(0) f(-1) f(2)

algebra - find the indicated outputs for f(x = 3x^2 -5x f(0)= f(-1)= f (2)=

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)5^2-4x F(0)= f(-1)= f(2)=

Algebra - Find the indicated outputs for f(x)= 5 x(2) - 4x. F(0)= f(-1)= f(2)=